Desalination Concentrate Management - Ladewig, Bradley; Asquith, Benjamin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book examines five methods used for concentrate management, namely; disposal to surface water, disposal to sewerage, deep well injection, land applications and evaporation ponds. In particular, the book focuses on the design, siting, cost, and environmental impacts of these methods. While these methods are widely practiced in a variety of settings already, there are many limitations that restrict the use of certain disposal options in particular locations.
Characteristics of Membrane Concentrate -- Process Feasibility -- Disposal to Surface Water -- Deep Well Injection -- Spray Irrigation -- Evaporation Ponds.
Keywords: Chemistry; Chemical engineering; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Water pollution; Chemistry; Industrial Chemistry/Chemical Engineering; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Geoengineering, Foundations, Hydraulics; Electronic books